A biocomplex to repair experimental critical size defects associated with photobiomodulation therapy - Buchaim, Daniela Vieira [UNESP]; Andreo, Jesus Carlos; Pomini, Karina Torres; Barraviera, Benedito [UNESP]; Ferreira, Rui Seabra [UNESP]; Duarte, Marco Antonio Hungaro; Alcalde, Murilo Priori; Reis, Carlos Henrique Bertoni; de Bortoli Teixeira, Daniel; de Souza Bueno, Cleuber Rodrigo; Detregiachi, Cláudia Rucco Penteado; Araujo, Adriano Cressoni; et al. (FapUNIFESP (SciELO), 2022)
Background: The association of scaffolds to repair extensive bone defects can contribute to their evolution and morphophysiological recomposition. The incorporation of particulate biomaterials into three-dimensional fibrin bioproducts together with photobiomodulation therapy (PBM) has potential and can improve regenerative medicine procedures. The objective of this experiment was to evaluate the effects of PBM therapy on critical size defects filled with xenogenic bone substitute associated with fibrin biopolymer. Methods: A critical defect of 8 mm was performed in 36 Wistar male adult rats that were divided into four groups. Groups BC and BC-PBM were defined as controls with defects filled by a clot (without or with PBM, respectively) and groups XS and XS-PBM that comprised those filled with biocomplex Bio-OssTM in association with fibrin biopolymer. PBM was applied immediately after the surgery and three times a week every other day, with the parameters: wavelength of 830 nm, energy density 6.2 J/cm2, output power 30 mW, beam area of 0.116 cm2, irradiance 0.258,62 W/cm2, energy/point 0.72 J, total energy 2.88 J. Fourteen and 42 days after the surgery, animals were euthanatized and subjected to microtomography, qualitative and quantitative histological analysis. Results: The BC-PBM and XS-PBM groups had a similar evolution in the tissue repair process, with a higher density of the volume of new formed bone in relation to the groups without PBM (p = 0.04086; p = 0.07093, respectively). Intense vascular proliferation and bone deposition around the biomaterial particles were observed in the animals of the groups in which biocomplex was applied (XS and XS-PBM). Conclusion: PBM therapy allowed an improvement in the formation of new bone, with a more organized deposition of collagen fibers in the defect area. Biocomplex favored the insertion and permanence of the particulate material in bone defects, creating a favorable microenvironment for accelerate repair process.
Keywords: Biomaterials; Bone regeneration; Bone substitutes; Fibrin sealant; Low-level laser therapy; Photobiomodulation therapy